2016
DOI: 10.4149/gpb_2015040
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and electroretinogram after intravitreal injection of methotrexate in an experimental rabbit model

Abstract: The aim of this study was to explore the changes in electroretinogram of rabbit retina and apoptosis in methotrexate-induced toxicity. Rabbits were divided into 5 groups. Group I served as control in which saline solutions was injected intravitreally. Methotrexate (800 μg, 1.76 μmol) was injected into the vitreous of both eyes of rabbits groups II, III, IV and V by an insulin injector with a 26 gauge needle under general anesthesia. Retinal function was assessed by electroretinogram (ERG) after 2, 4, 10 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…6 Eman et al showed a significant reduction in a-wave and b-wave on electroretinogram (ERG), raised relative caspase-3 activity and typical ladder pattern of internucleosomal fragmentation on gel electrophoresis (characteristic of apoptosis) on injecting 800 μg/0.1 mL MTX into the vitreous cavity. 7 Single intravitreal injection of 400 and 800 μg of MTX did not show significant anti-inflammatory effects in experimentally induced uveitis in rabbits. 8 However, Deng et al 9 found intravitreal MTX to be better than dexamethasone in reducing inflammation in experimentally induced bacterial endophthalmitis with Staphylococcus epidermidis in rabbits.…”
Section: Methotrexatementioning
confidence: 88%
See 1 more Smart Citation
“…6 Eman et al showed a significant reduction in a-wave and b-wave on electroretinogram (ERG), raised relative caspase-3 activity and typical ladder pattern of internucleosomal fragmentation on gel electrophoresis (characteristic of apoptosis) on injecting 800 μg/0.1 mL MTX into the vitreous cavity. 7 Single intravitreal injection of 400 and 800 μg of MTX did not show significant anti-inflammatory effects in experimentally induced uveitis in rabbits. 8 However, Deng et al 9 found intravitreal MTX to be better than dexamethasone in reducing inflammation in experimentally induced bacterial endophthalmitis with Staphylococcus epidermidis in rabbits.…”
Section: Methotrexatementioning
confidence: 88%
“…6 Eman et al showed a significant reduction in a-wave and b-wave on electroretinogram (ERG), raised relative caspase-3 activity and typical ladder pattern of internucleosomal fragmentation on gel electrophoresis (characteristic of apoptosis) on injecting 800 μg/0.1 mL MTX into the vitreous cavity. 7…”
Section: Immunosuppressantsmentioning
confidence: 99%
“…Repeated injections are considered feasible without retinotoxicity [ 10 ], and OCT studies reveal structural recovery after treatment with ivMTX [ 11 ]. However, an experimental study in rabbits analyzed retinal function by ERG after ivMTX, showing significant reduction of the amplitude of a- and b-waves [ 6 ]. These results suggest that there are possible subclinical complications of ivMTX which can only be assessed by ERG.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report demonstrated the efficiency of intravitreal injections of methotrexate (ivMTX) in treating IOL [ 5 ]. An experimental study in rabbits revealed the retinal cytotoxicity of ivMTX [ 6 ]. However, few reports have evaluated changes in retinal function after ivMTX administration in humans [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that high dose intravitreal MTX results in significant ultrastructural changes in the rabbit retina in varying severities. In another study, Aly and Ebrahim [16] assessed the effect of MTX toxicity on electroretinogram (ERG) and retinal caspase-3 activity which has an executive role in apoptosis of pigment epithelial cell, outer nuclear layer cell, and ganglion cells [17] after injection of a single dose of 800 µg MTX. They showed that intravitreal injection of MTX leads to a significant reduction in a-and b-waves with an increase in caspase-3 activity.…”
Section: Preclinical Studiesmentioning
confidence: 99%